2021
DOI: 10.1111/pai.13434
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar immunophenotypic signature in MIS‐C‐affected children

Abstract: Function study group. Heterozygous STAT1 Gain-of-function mutations underlie an unexpectedly broad clinical phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Few months after the onset of the pandemic, a series of reports around the world described clusters of children and adolescents presenting with a lifethreatening, hyperinflammatory syndrome, named Kawasakilike syndrome (8,12), Pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) (13) or Multisystem Inflammatory Syndrome in Children (MIS-C) (14). The pathogenesis of MIS-C is still unknown, although it has been suggested that this syndrome occurs while the immune system is activated against the SARS-CoV-2 virus (15). The host immune system in pediatric patients responses excessively to SARS-CoV-2 infections and lead to the multisystem inflammatory syndrome in children (MIS-C).…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…Few months after the onset of the pandemic, a series of reports around the world described clusters of children and adolescents presenting with a lifethreatening, hyperinflammatory syndrome, named Kawasakilike syndrome (8,12), Pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) (13) or Multisystem Inflammatory Syndrome in Children (MIS-C) (14). The pathogenesis of MIS-C is still unknown, although it has been suggested that this syndrome occurs while the immune system is activated against the SARS-CoV-2 virus (15). The host immune system in pediatric patients responses excessively to SARS-CoV-2 infections and lead to the multisystem inflammatory syndrome in children (MIS-C).…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…In previous studies, it has also been demonstrated that children with MIS-C had specific T and B cell subsets in the peripheral blood. Consiglio et al ( 22 ) found higher central memory and effector memory CD4 + T cells, with lower naïve CD4 + T cells, and Licciardi et al ( 19 ) revealed a characteristic B cell subset in MIS-C patients with low levels of transitional B cells and high levels of switched memory B cells and marginal zone B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who fulfilled the MIS-C definitions ( 18 , 19 ): age <21 years presenting with fever, laboratory evidence of inflammation, multisystemic (>2) organ involvement and severe clinical illness requiring hospitalization, no alternative plausible diagnosis with evidence of current or recent infection of SARS-CoV-2 by RT-PCR, and positive results of anti-SARS CoV-2 antibodies detected by chemiluminescence immunoassay (CLIA). In the MIS-C group, we collected the blood sample at admission, before the start of the IVIG/steroid therapy.…”
Section: Methodsmentioning
confidence: 99%
“…11 MIS-C is an antibody and immunocomplex-mediated disease that occurs approximately 3 to 4 weeks after the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. 1 2 3 Vitamin D may reduce complications related to SARS-CoV-2 and “Kawasaki disease” by modulating immunity. 12 13 14 For example, an association was found between coronary artery anomaly and low vitamin D levels in Kawasaki disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…MIS-C is thought to have been caused by an overreaction to the coronavirus by the immune system. 3 Multiple factors—being overweight, asthmatic, or being of Asian or black ethnic origins—have been reported vis-à-vis the MIS-C. 4 There is an association between these conditions and vitamin D deficiency, which explains why MIS-C is more common in the patients with the abovementioned conditions. 4 Vitamin D may have anti-inflammatory effects by many mechanisms.…”
Section: Introductionmentioning
confidence: 99%